Prospective associations of C-reactive protein (CRP) levels and CRP genetic risk scores with risk of total knee and hip replacement for osteoarthritis in a diverse cohort. Issue 8 (August 2018) - Shadyab, A.H.; Terkeltaub, R.; Kooperberg, C.; Reiner, A.; Eaton, C.B.; Jackson, R.D.; Krok-Schoen, J.L.; Salem, R.M.; LaCroix, A.Z.
Summary: Objective: To examine associations of high-sensitivity C-reactive protein (CRP) levels and polygenic CRP genetic risk scores (GRS) with risk of end-stage hip or knee osteoarthritis (OA), defined as incident total hip (THR) or knee replacement (TKR) for OA. Design: This study included a cohort of postmenopausal white, African American, and Hispanic women from the Women's Health Initiative. Women were followed from baseline to date of THR or TKR, death, or December 31, 2014. Medicare claims data identified THR and TKR. Hs-CRP and genotyping data were collected at baseline. Three CRP GRS were constructed: 1) a 4-SNP GRS comprised of genetic variants representing variation in the CRP gene among European populations; 2) a multilocus 18-SNP GRS of genetic variants significantly associated with CRP levels in a meta-analysis of genome-wide association studies; and 3) a 5-SNP GRS of genetic variants significantly associated with CRP levels among African American women. Results: In analyses conducted separately among each race and ethnic group, there were no significant associations of ln hs-CRP with risk of THR or TKR, after adjusting for age, body mass index, lifestyle characteristics, chronic diseases, hormone therapy use, and non-steroidal anti-inflammatory drug use. CRP GRS were not associated with risk of THR or TKR in any ethnic group. Conclusions: Serum levels of ln hs-CRP and genetically-predicted CRP levels were not associated with risk of THR or TKR for OA among a diverse cohort of women.